Potential Of Pseudomonas fluorescens As Plant Growth Promoting Bacteria - Claudia Ayesha; Linda Advinda; Violita Violita; Dezi Handayani (Jurnal Serambi Biologi, 2023)
Plant growth promoting bacteria or Plant Growth Promoting Rhizobacteria (PGPR) are soil bacteria found in the root area which function to increase plant growth. Most of them came from the Gram-negative group with the highest number of strains from the genus Pseudomonas. Pseudomonas fluorescens is able to produce IAA, siderophores and phosphate solubilizing compounds, fixes nitrogen and exhibits plant growth promoting activity. Therefore, this bacterium is very potential as a PGPR. This study aims to collect and analyze articles related to the potential of Pseudomonas fluorescens as a plant growth promoting bacterium. This type of research is research that uses internet sources from the Google Scholar database. The stages consist of identification, screening, eligibility and acceptance. Based on the articles collected, it was found that Pseudomoas fluorescens is one of the Plant Growth Promoting Rhizobacteria (PGPR). PGPR affects plant health and soil fertility by offering an excellent combination of properties that are useful in promoting plant growth, namely producing IAA and siderophores, dissolving phosphate, fixing nitrogen and exhibiting plant growth promoting activity.